A 3-Year retrospective evaluation of the clinical performance of fiber posts - Amaral, Marina [UNESP]; Coppo, Priscilla Pessin; Rosalem, Cíntia Gonçalves Carvalho; Suaid, Fabricia Ferreira; Guerra, Selva Maria Gonçalves (FapUNIFESP (SciELO), 2015)
This retrospective study evaluated the clinical outcome of 139 teeth restored with carbon fiber posts after 3 years of placement, considering the amount of remaining dentin as the main variable. Eighty-one patients received the fiber posts within a period of 16 months and were recalled after 3 years. The tooth type, amount of remaining dentin, and prosthetic crown material were evaluated. No loss of post or core retention was detected after 3 years of follow up. During the observed time, root or post fracture and secondary caries were not recorded. Only one failure concerning endodontic treatment was detected. The amount of remaining dentin was not an important characteristic in the restorative failure of endodontically treated teeth restored with carbon fiber posts within 3 years.
Keywords: Ceramics; Clinical research; Dental restoration failures; Endodontically treated teeth; Survival analysis